Health-Enhancing Physical Activity among University Students in Shanghai: A Case of Shanghai University of Sport - Xu, Shiwen (2018)
Shanghai is a highly populated city with over 430 000 university students. Finding out the level“, motivations and constraints of health-enhancing physical activity (HEPA) participation among university students is a crucial reference for policy makers to further promote HEPA participation. Therefore, the aim of this research is to find out the characteristics of the university students participating in HEPA. A quantitative data (n=226) was collected in order to answer the research questions about the level, motivations and barriers of HEPA participation among university students in Shanghai, and also to find out possible solutions in respect of promoting HEPA participation. The International Physical Activity Questionnaire (IPAQ) was used to measure the HEPA participation rate. The adapted Physical Activity Measure Revision (MPAM-R) was used to identify the motivations behind PA participation. SPSS 17.0 was applied to analyze all statistical data from 226 students in Shanghai University of Sport (SUS). The main results of this thesis revealed the most popular exercises among university students are walking, running and swimming. Students in SUS have a relative higher HEPA participation compared to their counterparts worldwide. Female students have a lower participation rate than males. Different genders participated in HEPA for different reasons, for which males are for health while females for appearance. The most reported constraints for HEPA participation for both male and female university students is lack of time. The main conclusions indicate that universities should further develop HEPA programs in order to make sure both male and female students have accessibility to their preferred exercises. For example, prolonging the opening hours of sport stadiums and providing sport classes were revealed in the study.